(untitled) (diségno, 2022)
In recent decades, especially since the 1990s, the growing of training courses in the area of design has brought about an exceptional variety of design declinations. A sort of euphoric openness towards the most varied thematic areas, from product to service, from interiors to fashion and, of course, to communication, a discipline transversal to multiple project spaces, has favored a pulviscular articulation also in the sectors adjacent to design, such as, undoubtedly, drawing. [read more]